Formulasi sediaan pasta gigi herbal ekstrak etanol bunga telang (Clitoria ternatea L.) dan uji aktivitas antibakteri terhadap bakteri Streptococcus mutans - Rati , Yuliandini; Dalimunthe , Gabena Indrayani; Lubis, Minda Sari; Nasution , Haris Munandar (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Dental and oral disease is a disease experienced by almost half of the world's population (3.58 billion people). Gum (periodontal) disease is the 11th most common disease in the world. One of the dental and oral diseases that has a fairly high prevalence in Indonesia is dental caries. The aim of this research was to evaluate the physical quality of toothpaste preparations with various concentrations (10%, 30% and 50%) and to determine the antibacterial activity of ethanol extract toothpaste preparations from butterfly pea flowers (Clitoria ternatea L.) against the growth of Streptococcus mutans bacteria.The stages of this research included processing plant materials, making ethanol extract of butterfly pea with ethanol 96% solvent, characterization examination, screening of phytochemicals, making herbal toothpaste preparations of butterfly pea extract, preparation evaluation, and testing the antibacterial activity of butterfly pea toothpaste against Streptococcus mutans using the well-diffusion method. Based on the research results, it can be seen that the antibacterial activity of the formula with the greatest zones of bacterial inhibition is F1 and F2, namely 21.85 mm and 21.15 mm with very strong inhibition criteria. The conclusion of this study is that herbal toothpaste with butterfly pea extract can prevent and treat dental caries caused by Streptococcus mutans bacteria.